ANALISIS EKONOMI PENGGUNAAN JASA OUTSOURCING UNTUK PENGADAAN ALAT TRANSPORTASI PT XYZ BANJARMASIN - ., Hermansyah; Suprianto, Teguh (INTEKNA, 2012)
About problem which faced by firm all this time is how to maintenance  and looking after all vehicle in good condition. Operational car maintenance all this time did by mechanical corporate and also by car workshop. In height cost maintenance and acquisition tool which issued by PT. XYZ for operational corporate, cause to need it firm to take into account alternative any other for transportation tool procurement by the way of outsourc-ing . In this research outsourcing  procurement service is seen of PT XYZS angle. This rese-arch did by economic analysis to do feasibility study in does outsourcing than by un-dertaking alone management. Economic analysis that is done is by use of analysis NPV (Net Present Value) and IRR (Internal of Returns Rate). After knows that by use of ser-vice outsourcing more advantages therefore analysis further is do election to service pro-vider judgment outsourcing. Judgment election  transportation tool by use of method AHP (Analytical Hierarchy Process). Base alternative observational result investment buys alone operational vehicle get NPVS point as big as Rp.840.440.945 and Internal Rate Of Return as big as 51 %. Meanwhile by use of service outsourcing  one that is chosen by use of method AHP that gets service outsourcing  the most corresponds to criteria firm, and is chosen on service outsourcing 2 get NPVS points as big as Rp 1.386.000.000 ,- and Internal Rate Of Return as big as 77% , therefore analysis judgment in observational so in accordance with corporate decision making. service outsourcing  more advantages to be appealed is brought off own.